En Bloc Resection of the Pancreatic Head and Second Part of Duodenum for a Duodenal Gastrointestinal Stromal Tumor: A Multi-Media Report - Frampton, Adam E; Bong, Jan J; Kyriakides, Charis; Cohen, Patrizia; Jiao, Long R (JOP. Journal of the Pancreas, 2010)
Duodenal gastrointestinal stromal tumors are rare tumors. When these tumors arise from the second part of the duodenum they can easily be misdiagnosed as a pancreatic head cancer. A case of a 37-year-old female presenting with a one-year history of right upper quadrant pain is described here, who was subsequently found to have a mass in the head of the pancreas. Computed tomography scans showed a 2 cm hypervascular lesion lying between the head of pancreas and the second part of the duodenum, suggestive of a neuroendocrine tumor, and confirmed by endoscopic ultrasound scan. She underwent a pancreatic head resection with duodenal segmentectomy. Histopathological and immunohistochemical analysis revealed the tumor to be peri-ampullary duodenal gastrointestinal stromal tumor not invading the pancreas. Duodenal gastrointestinal stromal tumor can have a wide spectrum of clinical presentation. The accurate diagnosis of duodenal gastrointestinal stromal tumor is essential for determining the appropriate surgical intervention. In our case, a conservative surgical approach was utilised therefore avoiding a formal pancreaticoduodenectomy. Image: Excision of the second part of duodenum.